Uslub: Questions and Answers in the Qur’an - Suhaimi, Suhaimi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
One of the uslubs or language styles mentioned in the Quran for expressing its sacred messages is question and answer (sual wa jawab), where a question is followed by its answer. This style of language has certainly attracted the attention of many parties, especially the scholars of the Quran, or mufassirin, whose thoughts and expertise are in direct contact with the holy words, as well as Arabic linguists, especially those related to balaghah. Scholars' perspectives on revealing the secrets of these questions and answers differ according to their scientific backgrounds, but all of them appear to be urgent in order to strengthen our awareness of the truth of the Divine Word that Allah revealed to His Messenger Muhammad (peace be upon him). The questions and answers (uslub) implicitly seem like an extremely important style or learning method to be applied in communicating with other parties. Among the forms of questions and answers (uslub) in the Qur'an that are interesting to observe is "uslub al-hakim," which is literally interpreted as the style of a wise man. This article discusses some of the general characteristics of usul al-Quran.It also describes specific types of Quranic questions and answers. Hence, it aims to be a blessing for us in this life.